In the event : toward an anthropology of generic moments - Meinert, Lotte; Kapferer, Bruce (Berghahn Books, 2015)
Events are ""generative moments"" in at least three senses: events are created by and condense larger-scale social structures; as moments, they spark and give rise to new social processes; in themselves, events may also serve to analyze social situations and relationships. Based on ethnographic studies from around the world-varying from rituals and meetings over protests and conflicts to natural disasters and management-this volume analyzes generative moments through events that hold the key to understanding larger social situations. These events-including the Ashura ritual in Bahrain, social